2001
DOI: 10.1088/0031-9155/46/5/307
|View full text |Cite
|
Sign up to set email alerts
|

A multiple source model for 6 MV photon beam dose calculations using Monte Carlo

Abstract: A multiple source model (MSM) for the 6 MV beam of a Varian Clinac 2300 C/D was developed by simulating radiation transport through the accelerator head for a set of square fields using the GEANT Monte Carlo (MC) code. The corresponding phase space (PS) data enabled the characterization of 12 sources representing the main components of the beam defining system. By parametrizing the source characteristics and by evaluating the dependence of the parameters on field size, it was possible to extend the validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
85
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 38 publications
1
85
0
3
Order By: Relevance
“…The filter is a major contributor of scattered radiation in the treatment head (Chaney et al 1994, Fix et al 2001 and can lead to higher doses outside the treatment field , Kry et al 2010, O'Brien et al 1991.. Due to the non-uniform shape of the flattening filter, the beam energy distribution will vary with off-axis distance, creating challenges for dose calculation algorithms. One way of removing these unfavourable properties of conventional clinical radiation beams would be to remove the flattening filter.…”
Section: Introductionmentioning
confidence: 99%
“…The filter is a major contributor of scattered radiation in the treatment head (Chaney et al 1994, Fix et al 2001 and can lead to higher doses outside the treatment field , Kry et al 2010, O'Brien et al 1991.. Due to the non-uniform shape of the flattening filter, the beam energy distribution will vary with off-axis distance, creating challenges for dose calculation algorithms. One way of removing these unfavourable properties of conventional clinical radiation beams would be to remove the flattening filter.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[21][22][23] It has been shown that if the electron beam above the target is modeled accurately and the particles are accurately transported through the beam-generating devices to the PS plane, the dose calculation using that PS file is able to match measured dose. 9,16,18,23,24,[36][37][38] One limitation of directly using the PS file is the lack of flexibility to adjust the data for use with accelerators with slightly different outputs. A second limitation is the introduction of a systematic error, termed latent or remnant variance, as recently mentioned by Sichani and Sohrabpour 25 and Fippel et al 34 and described in detail by Sempau et al 39 This systematic error is due to the limited size of the PS file, which results in a finite variance for a calculated quantity, e.g., dose, using a finite-sized PS file as input.…”
Section: Introductionmentioning
confidence: 99%
“…Apart form using analytical source models or the PS file itself as a source model, another approach, which overcomes these limitations, is to create a histogram-based source model based on the PSD. 8,[12][13][14][15][16][17] By sampling the initial parameters of a particle from these histogram distributions, virtually no particle is reused, thereby reducing the latent variance. A further advantage of histogram-based source models is that the sampling is faster than reading particles from a PS file.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations